Coming to know Indigeneity: Epistemologies of ignorance in the 2003–2015 Ontario Canadian and World Studies Curriculum. Issue 4 (20th November 2018) - Schaefli, Laura M.; Godlewska, Anne M. C.; Rose, John
Abstract: This article investigates the portrayal of colonialism and Indigenous peoples in curricula and textbooks in the province of Ontario, Canada. The analysis is focused on the curricular documents and texts that constituted Ontario's social studies and Canadian and World Studies stream between 2003 and 2015, which have informed the understanding of a generation of Ontarians. Drawing on recent work on epistemologies of ignorance, we demonstrate how segregation and past placement of Indigenous content, omission of Indigenous critical perspectives, philosophies, and territories, denial of colonialism, and reinforcement of racialized hierarchies work to encourage logic of relation premised on Indigenous disappearance. Although nine textbooks associated with the 2003–2015 Canadian and World studies curriculum were reviewed by First Nations and Métis educators, critical Indigenous perspectives are frequently undermined in the texts through exclusion from chapter review questions, segregation of content, and imposition of settler voice. Although the Ministry of Education has created a new curriculum, the depth, and perniciousness of epistemologies of ignorance requires sustained involvement of First Nations, Métis and Inuit educators at all levels of curricular and text design, with special attention to the training of teachers.